MORE ON *∗ − CONNECTED - Kilinç, Selahattin (Matematichki Bilten, 2019)
In [4] \(**\)-connected, \(*\)-cl-connected and \(*\)-cl\(*\)-connected ideal space are introduced and studied by Modak and Noiri. We further study the properties of these sets and give a characterization of \(**\)-connected ideal space.